Bearing Capacity and Keying of Plate Anchor in Normally Consolidated Clay - Song, Zhenhe; Hu, Yuxia; Muelle, Erik (ISOPE, 2008)
In this paper, finite element analyses of plate anchor keying in Normally Consolidated (NC) clay were performed. Bearing capacity of plate anchors was investigated with various embedment ratios and pullout inclination angles. Both vented anchor base (no suction on rear face) and fully attached (bonded) anchor base were considered in the analysis. Anchor rotation was analysed using RITSS (Remeshing and Interpolation Technique with Small Strain model) method. It is found that the bearing capacities of inclined plate anchors are associated with both of the loading inclination angles and the anchor base conditions. The soil weight plays an important role in the bearing capacity analysis. The soil non-homogeneity has minor effect on anchor rotational behaviour.